Needs Analysis of Problem-Based Learning and Local Wisdom-Based E-Student Worksheet to Facilitate Students’ Critical Thinking Skills in Kinematics Learning - Rahmia Sri Fani; Emiliannur Emiliannur; Asrizal Asrizal; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
Twenty-first-century education requires students to develop critical thinking skills to analyze and solve complex problems, particularly in physics learning. However, students’ critical thinking skills in kinematics remain low because existing teaching materials, conceptual representations, and learning activities have not effectively supported problem-solving processes. This study aimed to analyze students’ needs as the basis for developing a Problem-Based Learning (PBL)-based E-Student Worksheet integrated with local wisdom to facilitate critical thinking skills in kinematics learning. The study employed a Research and Development (R&D) approach using the define stage of the 4D model. The participants were 25 students at SMAN 1 Sungai Geringging. Data were collected through teaching material analysis, student characteristics analysis, concept analysis, task analysis, learning objective analysis, critical thinking tests, questionnaires, and teacher interviews. The findings showed that students’ average critical thinking skills reached only 37%, categorized as low, with self-regulation as the lowest indicator (25%). Teaching material analysis revealed limited multimedia integration, adaptive characteristics, and contextual learning support, while concept analysis indicated inadequate alignment between existing materials and ideal kinematics concepts, particularly in projectile motion. These findings conclude that developing a PBL-based E-Student Worksheet integrated with local wisdom is necessary to provide contextual, interactive, and meaningful learning that improves students’ critical thinking skills.